A representative retinoid X receptor antagonist UVI3003 induced teratogenesis in zebrafish embryos. Issue 3 (3rd September 2014) - Zheng, Liang; Xu, Ting; Li, Daoji; Zhou, Junliang
Abstract Retinoid X receptor (RXR) interfering activity has been detected in different water resources. To study RXR disruptor‐induced toxicological effects on vertebrates, embryos of zebrafish (Danio rerio) were exposed to a representative RXR antagonist UVI3003. Results showed that the teratogenic index (LC50/EC50) of UVI3003 was as high as 5.4. UVI3003 induced multiple malformations of embryos, including deformed fins, reduced brains, small jaws, bent tails and edema in hearts, the degree of which became more severe with increasing exposure concentration. Although no significant difference was observed in the hatching rates between the exposure group and control, the whole body length was significantly reduced by 6.5% and 8.9% when exposed to 200 and 300 µg l−1 of UVI3003, respectively. The heart rate also significantly decreased by 8.8–50.2% during exposure. Further experiments revealed that the pharyngula stage was the most sensitive development phase in terms of embryo response to UVI3003. The results demonstrated severe teratogenicity of RXR antagonist in zebrafish embryos and provided important data for ecotoxicological evaluation of RXR antagonists. Copyright © 2014 John Wiley & Sons, Ltd.